FMOS: The fiber multiple-object spectrograph IV: Current status of OHS-based spectrograph - Iwamuro, F; Maihara, T; Ohta, K; Eto, S; Sakai, M; Akiyama, M; Kimura, M; Tamura, N; Noumaru, J; Karoji, H; Dolton, G; Lewis, I; et al. (2006)
The Fiber Multiple-Object Spectrograph for Subaru Telescope (FMOS) is quite large instrument composed of the prime focus unit, the fiber bundle unit, and the two infrared spectrographs. Among these units, a part of the prime focus unit and one of the spectrograph were transported from Kyoto University to the Subaru observatory in the middle of 2005. We present the optical and the mechanical components of the spectrograph, which was reassembled on the new floor of the Subaru dome. We also show the preliminary results of the optical alignment and the cooling test of the instrument at the summit of Mauna Kea.